The relationship between Calcitonin and Creatine kinase levels in sera of newly diagnosed Iraqi patients with coronary artery disease - ABDEEN, JWAN A.ZAINUL; IBRAHIM, SUHAD A. (International Journal of Psychosocial Rehabilitation, 2020)
One of the most serious heart diseases and May lead to sudden cardiac death is the coronary artery disease (CAD). Meanwhile, CAD diagnoses are very expensive and time-consuming. The propose of this work was to evaluate the levels of calcitonin (CT) and serum creatine kinase (CK) in newly diagnosed CAD patients. This study was conducted on 54 patients with CAD disease, including (23 female and 31 male), with age for male patients (56.61 ± 9.71) and (56.27 ± 9.22) for female patients, in addition to 54 healthy volunteers, including (23 females and 31 males) groups of matched control. After obtaining serum samples from separate patient and control groups, the measuring values for CK and CT were done using ELISA method and the data of analysis was carried out using the SPSS. The results of the study showed statistically high significant serum CK activities (660.24 ± 27.275), (653.18 ± 34.747) in male and female patients respectively, compared to the control group (69.19 ± 8.299), (89.54 ± 10.998), respectively. Similarly, there was a significant increase in the level of CT in the male patients as compared to female patients as it was as mean± SD (10.48 ± 0.375), (9.56 ± 0.453), respectively. When compared to the control males and females, the mean was ± SD (8.82 ± 0.389), (8.44 ± 0.434), respectively. There was also a negative association between CT and CK (r = -0.065) in females and a positive relationship (r = 0.294) in males, both of which were unimportant. There was a negative relationship between CT and age, in both patient groups, when compared with the other group (control). In regard to the relationship between CK and age, the positive relationship (r = 0.034) had a negative correlation, in males (r = -0.178) and in females, when compared to the control groups. Age and gender variables and family history of diabetes were taken into account and it was found that the difference is significant between the two groups. Because the relationship of serum levels CT and CK with CAD severity is unknown, the case presented here highlights the importance of serum CT and serum CK levels in differential diagnosis of coronary disease (CAD).